Characteristics of Patients with Dermatologic Conditions in a Student-Run Free Clinic: A Retrospective Study - Hammond, Alexander; Smith, Kristin; Welborn, Macartney; Dukharan, Victoria; Daga, Anshul; Warpinski, Chloe; Nguyen, Oliver; Motwani, Kartik; Motaparthi, Kiran (Journal of Student-Run Clinics, 2023)
Background: The Equal Access Clinic is a free, student-run clinic affiliated with the University of Florida in Gainesville, Florida. Four days a week, a general clinic is held at various sites, providing free healthcare to patients in North Florida. Once a month, a specialty clinic for dermatology is held based on a referral system from general clinics. We aimed to characterize patients’ demographics and diagnoses who received dermatologic care at a free clinic in North Florida. Methods: A retrospective chart review was completed for patients seen at Equal Access Clinic for a dermatology diagnosis from 2013 to 2020 (n=864). Results: One third of patients were seen for a chronic dermatology condition. Patients who were white and higher earners were more likely to travel further distances for care. Conclusions: These findings highlight the importance of improving access of dermatology care to underserved areas and may be accomplished in part by increasing access to transportation to clinics. Limitations include the retrospective nature of our chart review and the reliance on zip code to estimate median household income. Additionally, the patients in this study were seen by primary care physicians, rather than dermatologists.